Quality of clinical guidelines: It matters as it impacts patient care - KANİ, HALUK TARIK (My University, 2024)
Clinical guidelines are of vital importance in providing healthcare professionals with updated evidence‐based recommendations eventually aiming to improve patient care and outcomes. Nonetheless, guidelines often lack evidence or transparency in how evidence was interpreted and graded. Historically, the development of guidelines was done in GOBSAT ‐ (‘Good old men sitting around the table’) style by collating data from literature mixed with experience‐based opinions. These guidelines often fail to address some of the essential and pivotal factors that are fundamental to high‐quality guidelines. In addition, they often lack applicability, practicality, and the outcomes that really matter to patients. In recent decades, there has been a shift to making the guideline development process more transparent, robust, and evidence‐based, whilst involving multiple stakeholders (e.g., patients, general practitioners, or paramedics). Within the editorial board of United European Gastroenterology (UEG) Journal, a Guidelines Taskforce was established that aims at fostering a heightened awareness among readership and contributing authors on the quality of guidelines and the critical importance of transparency throughout the guideline development process. In order to scrutinize the adherence to the standards of guidelines within the field of gastroenterology, the Taskforce collected and evaluated all 16 guidelines1–17 published in the UEG Journal between January 2020 and March 2022. The assessment was conducted by four reviewers, who were equipped with the necessary expertise through participation in the International Guideline Training and Certification (INGUIDE) program (https://inguide.org/).
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Gastroenteroloji-(Hepatoloji); Onkoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Gastroenterology and Hepatology; Oncology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; GASTROENTEROLOJİ VE HEPATOLOJİ; ONKOLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; GASTROENTEROLOGY & HEPATOLOGY; ONCOLOGY; Gastroenteroloji; Gastroenterology; AGREE II; assessment; gastroenterology; GRADE; guideline; quality